The Effect Of Motivation On Visiting Decisions Mediated By Perception And Satisfaction At Pandawa Beach - Mohamad Zayyad; Titien Damayanti; Widi Hardini (LP2M IAIN Palopo, 2025)
This study examines the influence of motivation and perception on tourists’ visiting decisions, with satisfaction as a mediating variable, grounded in the Expectation Disconfirmation Theory (EDT). A quantitative approach was employed with 240 respondents, consisting of domestic and international tourists who had visited or were currently visiting Pandawa Beach, selected through accidental sampling. Data were analyzed using Structural Equation Modeling–Partial Least Square (SEM-PLS). The findings reveal that motivation has a direct and significant effect on both satisfaction and visiting decisions. Perception also contributes to enhancing satisfaction, although its direct impact on visiting decisions varies across tourist segments. Satisfaction acts as a key mediating factor linking motivation and perception to visiting decisions. These results enrich the theoretical understanding of tourist behavior and provide practical insights for Pandawa Beach management to improve service quality, comfort, and facilities in order to strengthen tourist satisfaction and encourage repeat visitation.